1995
DOI: 10.1111/j.1651-2227.1995.tb13582.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal versus intravenous administration of midazolam to children undergoing small bowel biopsy

Abstract: Sixty-three children under the age of 9 years were randomized to receive intravenous (group A, n = 33) or intranasal (group B, n = 30) midazolam as sedation for small bowel biopsy. Mean doses of midazolam given to produce adequate sedation were 0.31 mg (kg body weight)-1 in group A and 0.34 mg (kg body weight)-1 in group B (NS). Four children in group A and 10 children in group B required additional doses to maintain adequate sedation throughout the biopsy procedure (p < 0.05). There was no significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Previous studies using midazolam as an anaesthetic agent have concluded that the drug, when given intranasally, is an effective sedative and amnestic agent [12][13][14][15][16][17][18][19][20][21][22] . These studies have improved our understanding of the drug, the pros and cons of various routes of administration and its pharmacodynamic and pharmacokinetic properties [12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using midazolam as an anaesthetic agent have concluded that the drug, when given intranasally, is an effective sedative and amnestic agent [12][13][14][15][16][17][18][19][20][21][22] . These studies have improved our understanding of the drug, the pros and cons of various routes of administration and its pharmacodynamic and pharmacokinetic properties [12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…A pediatric study comparing intranasal midazolam to IV administration for small bowel biopsy by capsule concluded that the IV route was preferable, because fewer doses of medication were needed to maintain sedation. Furthermore, intranasal midazolam caused substantial local discomfort (61). Oral midazolam tastes bitter, even with flavoring agents added (46,51).…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…However, the dosage used to initiate and maintain sedation show dramatic differences. Most reports to date have been case series of midazolam used in patients of diverse age groups (from 3 days to 18 years of age), with doses ranging from 25 to 300 μ g/kg administered as a bolus injection, and 24–400 μ g/kg/h administered as a continuous infusion (4–8). In a multicentre pilot study, Anand et al.…”
Section: Introductionmentioning
confidence: 99%